Population genetics and evaluation of diallel cross of four red tilapia populations in Malaysia / Kayal Vizi a/p Karuppannan - Karuppannan, Kayal Vizi (2012)
Tilapia is an important farmed freshwater fish in Malaysia. Tilapia farming was introduced in Malaysia in the 1940’s. In 2003, tilapia accounted 21,417 tons of total freshwater aquaculture production. Red hybrid is the most popular tilapia species cultured in Malaysia. One of the constraints faced by the industry is quality of fries. There are quite a number of private hatcheries in Malaysia producing tilapia fries and not much is known about their quality with respect to their genetic variability. Thus this study attempted to characterize the four study populations and one standard population, which were PKPS (PS), Bentong (BT), Enggor (EG), Negeri Sembilan (NS) and Gift (GT) as control population using 20 polymorhic Microsatellite markers. Gift population is Nile tilapia. Their dendogram relationship showed that the hetrozygosity value was high, which indicated the presence of high genetic variability among the five populations. As a continuation, Diallel Crossing was started among four populations, which were PKPS (PS), Bentong (BN), Enggor (EG) and Negeri Sembilan (NS). Attention given to two traits, which were Growth and Survival. In Growth Factor, trait studied was Specific Growth Rate. In Survival, Egg Hatchability, Fry Survival and Adult Fish Survival were the three parameters focused on. As a outcome of this study, managed to produce broodstocks with known genetic attributes through quantitative genetics for fast growth rates based on high heritability, high additive variance and low environmental effects.